Anlageberatung Das System der zivilrechtlichen Haftung von Kreditinstituten - Krimphove, Dieter

Generation of Vector Patterns through Reseeding of Multiple-Polynomial LFSRs - Hellebrand, Sybille; Tarnick, Steffen; Rajski, Janusz; Courtois, Bernard
Keywords: WORKSHOP

Generation of Vector Patterns through Reseeding of Multiple-Polynomial LFSRs - Hellebrand, Sybille; Tarnick, Steffen; Rajski, Janusz; Courtois, Bernard
Keywords: WORKSHOP

Complexity results for the default- and autoepistemic logic - Steffen, Eckhard (Computer Science Logic)

Experimental Results to Interprocessor Communication in Distributed Transputer-Systems - Ginthör, Robert; Platzner, Marco; Weiss, Reinhold (Proceedings of the 1st Austrian-Hungarian Workshop on Transputer Applications)

Contribution to the AC-analysis of resonant converters; analysis of the series-parallel resonant converter including effects of parasitics and lossless snubbers for optimized design - Fröhleke, Norbert; Kunze, Jürgen; Fiedler, A.; Grotstollen, Horst (APEC '92 Seventh Annual Applied Power Electronics Conference and Exposition)

Resonant power supply for barrier discharge UV-excimer sources - Kunze, Jürgen; Fröhleke, Norbert; Grotstollen, Horst; Margaritis, Basile; Locken, F. (Conference Record of the 1992 IEEE Industry Applications Society Annual Meeting)

Hilbert, Zermelo und die Institutionalisierung der mathematischen Logik in Deutschland - Peckhaus, Volker (Berichte zur Wissenschaftsgeschichte)
Rezensionen: MR 93d:01046 (Charles F. Kielkopf); Zbl. Math. 756.01034 (I. Grattan-Guinness).

Wozu Algebra der Logik? Zum Lebenswerk von Ernst Schröder [Abstract] - Peckhaus, Volker (III. Österreichisches Symposion zur Geschichte der Mathematik. Neuhofen an der Ybbs, 8. bis 14. November 1992. Umwege, Abschneider und Sackgassen ... über Abweichungen vom „normalen“ Gang der Entwicklung. Kurzfassungen der Vorträge)

Arithmetik — Logik — absolute Algebra. E. Schröders Suche nach einer universalen Theorie der Verknüpfungen [Abstract] - Peckhaus, Volker (Deutsche Mathematiker-Vereinigung. Jahrestagung 13.–18.9.1992 in Berlin. Vortragsauszüge)